Analysis and Design of Blood Transportation in Bangkok Metropolitan Region A Case Study for the National Blood Center, Thai Red Cross Society - ปฐมศิริ, สมชาย; สุขาบูรณ์, ประภัสสร (Frontiers in Engineering Innovation Research, 2011)
Everyday, the demand for blood is enormous in order to save lives. Quick and safe blood service is crucial for the efficiency of medical treatment. However, distribution cost of blood should be of important as well. In Bangkok Metropolitan Region, the individual hospital needs to send its vehicle to pick up the requested blood at the National Blood Center (NBC), Thai Red Cross Society. On average, there are approximately 74 hospitals sent various kinds of vehicles to wait and pick up blood between I - 300 units from the NBC. With the current individual pick-up system, the transportation cost is excessive due to too many empty trips. This research paper presents the results from the study and analysis of the current blood transportation system. The new design is proposed based on the management science and business logistics concept. The problem is modeled as the vehicle routing problem (VRP) and solved by the Clarke and Wright's heuristic method. By testing with the real data, the results show that a lot of trips and total distance can be saved. Potentially, the transport efficiency could be increased by 68.53%. The paper also discusses about the business model for implementing such concept at the NBC.